Кон Nancy Tuana et al. (Ed.), Revealing Male Bodies: Për Nancy Tuana et al. (Ed.), Revealing Male Bodies - Ivanovska, Marija; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2002)
Author(s): Marija Ivanovska | Марија Ивановска Title (Macedonian): Кон Nancy Tuana et al. (Ed.), Revealing Male Bodies Title (Albanian): Për Nancy Tuana et al. (Ed.), Revealing Male Bodies Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 3 (Summer 2002) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 199-200 Page Count: 2 Citation (Macedonian): Марија Ивановска, „Кон Nancy Tuana et al. (Ed.), Revealing Male Bodies“, Идентитети: списание за политика, род и култура, т. 1, бр. 3 (лето 2002): 199-200. Citation (Albanian): Marija Ivanovska, „Për Nancy Tuana et al. (Ed.), Revealing Male Bodies“, përkthim nga Maqedonishtja Lindita Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 3 (Summer 2002): 199-200.